Early Inequality and Industrialization: Introduction - Lindert, Peter H. (Journal of Income Distribution®, 2000)
Seeking to enrich our understanding of inequality movements, economic historians have used new data to illuminate the earlier darkness that Kuznets urged us to explore. To explore earlier worlds without income tax returns or modern household surveys, they have turned to non-income measures of purchasing power and well-being. The articles in this issue give a good sampling from this new wave of economic history of inequality. Copyright 2000 Elsevier Science Inc. All rights reserved.